Understanding of family medicine in Africa: A qualitative study of leaders' views - Moosa, S.; Downing, R.; Mash, B.; Reid, S.; Pentz, S.; Essuman, A. (British Journal of General Practice, 2013)
Background The World Health Organization encourages comprehensive primary care within an ongoing personalised relationship, including family physicians in the primary healthcare team, but family medicine is new in Africa, with doctors mostly being hospital based. African family physicians are trying to define family medicine in Africa, however, there is little clarity on the views of African country leadership and their understanding of family medicine and its place in Africa. Aim To understand leaders' views on family medicine in Africa. Design and setting Qualitative study with in-depth interviews in nine sub-Saharan African countries. Method Key academic and government leaders were purposively selected. In-depth interviews were conducted using an interview guide, and thematically analysed. Results Twenty-seven interviews were conducted with government and academic leaders. Responders saw considerable benefits but also had concerns regarding family medicine in Africa. The benefits mentioned were: having a clinically skilled all-rounder at the district hospital; mentoring team-based care in the community; a strong role in leadership and even management in the district healthcare system; and developing a holistic practice of medicine. The concerns were that family medicine is: unknown or poorly understood by broader leadership; poorly recognised by officials; and struggling with policy ambivalence, requiring policy advocacy championed by family medicine itself. Conclusion The strong district-level clinical and leadership expectations of family physicians are consistent with African research and consensus. However, leaders' understanding of family medicine is couched in terms of specialties and hospital care. African family physicians should be concerned by high expectations without adequate human resource and implementation policies. © British Journal of General Practice.
Keywords: Africa; Definition; Family practice; Healthcare systems